The role of the therapeutic physical exercise and the complex recovery treatment for the patients with chronic degenerative diseases during the COVID-19 pandemic (Balneo and PRM Research Journal, 2022)
Abstract: Background: Osteoarthritis is one of the most common causes of pain and musculoskeletal disability and mainly affects the middle-aged and the elderly. The condition is chronic and disabling, it diminishes the patients' quality of life. Purpose. The study had the purpose of pointing out a possible connection between physical activity and the reduction of pain accompanied by the increased functional capacity in patients with chronic degenerative diseases during the COVID-19 pandemic. Material and method: The study was conducted on an outpatient basis for a period of 6 months on a number of 40 patients diagnosed with osteoarthritis. The evaluation of the patients was made at the beginning of the treatment and at its end (after 4 weeks), as well as at the control after 12 weeks.  Results: The study included a number of 40 patients over 45 years old, divided into 2 study groups: in group L1-knee osteoarthritis and in group L2 -hip osteoarthritis. The therapeutic physical exercise reduced pain and stiffness, and it also improved the functional capacity. Conclusions: Therapeutic physical exercise has an important role in the reduction of pain and disability, as well as in the increase in the quality of life, if it is done properly.Keywords: osteoarthritis, therapeutic physical exercise, pain, pandemic COVID-19